Burden, depression and fatigue in caregivers of lung transplantation candidates - OLGUN YILDIZELİ, ŞEHNAZ; TUFAN ÇİNÇİN, ASLI; ARIKAN, HÜSEYİN; ERYÜKSEL, SEMİHA EMEL (My University, 2023)
Objective: A great deal of social support is often provided by the caregiver of the patient. The purpose of this study is to evaluate the burden, fatigue and depression of the primary caregiver of patients with pulmonary transplantation candidates.Patients and Method: The primary caregivers of patients who were admitted to our hospital\"s pulmonary transplant outpatient clinic with end-stage pulmonary disease and no definite contraindications for transplantation, were included in the study. Zarit Burden Scale, Beck Depression Inventory and Short-Form (SF)-36 - Vitality questionnaires were applied to participants.Results: Thirty-nine patients and their caregivers were evaluated. Caregivers experienced low levels of depression. Mean score for Beck Depression Inventory was 12.7 +/- 10.1. Caregivers generally experienced medium levels of burden. Mean score for Zarit Burden Scale was 26.9 +/- 14.2. Majority of caregivers experienced clinically significant fatigue. Mean score for SF-36 - Vitality was 61 +/- 16.7. Zarit Burden Scale scores and Beck Depression Inventory scores showed a statistically significant positive correlation (r:0.962 p<0.01). Conclusion: Increased burden of caregivers of lung transplant candidates was associated with depression and fatigue. The presence of depressive symptoms is noteworthy even in the mild to moderate levels of burden. Supporting caregivers, has a great importance in terms of patient care and quality.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; patient quality; Lung transplantation; Caregivers; Burden; Depression; Fatigue; QUALITY-OF-LIFE; FAMILY CAREGIVERS; INTERNATIONAL SOCIETY; MARITAL-STATUS; HEART; DISTRESS; SUPPORT; REHABILITATION; THERAPY; IMPACT; Lung transplantation; Caregivers; Burden; Depression; Fatigue